2016
DOI: 10.1016/j.taap.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression and morphological alterations in the mammary gland after gestational exposure to bisphenol A, genistein and indole-3-carbinol in female Sprague-Dawley offspring

Abstract: This study aimed to evaluate the modifying effects of dietary genistein (GEN) and indole-3-carbinol (I3C) on early mammary gland development in female Sprague-Dawley offspring born to mothers exposed to BPA during gestation. Pregnant rats were treated with BPA25 or 250 μg/kg bw/day from gestational days 10 to 21 with or without dietary intake of GEN (250 mg/kg chow) or I3C (2000 mg/kg chow). At post-natal day (PND) 21, female offspring from different litters were euthanized for mammary gland development and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Delayed ductal growth was observed at PND30 after s.c. application of 250 μg/kg bw per day (equal to 8,925 μg/kg bw per day, GD7–23, Kass et al, 2015 [RefID 3402]). In another study, increased branching score and number of terminal ducts (TDs) and TEB+TDs are induced by 25 μg/kg bw per day (but not at 250 μg/kg bw per day) on PND21 after exposure from GD10 until GD21 (Grassi et al., 2016 [RefID 2387]). This finding is supported by a Tier 3 study (Leung et al, 2017 [RefID 3990]) showing also increased numbers of TEBs at 2.5 and 25 μg/kg bw per day.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Delayed ductal growth was observed at PND30 after s.c. application of 250 μg/kg bw per day (equal to 8,925 μg/kg bw per day, GD7–23, Kass et al, 2015 [RefID 3402]). In another study, increased branching score and number of terminal ducts (TDs) and TEB+TDs are induced by 25 μg/kg bw per day (but not at 250 μg/kg bw per day) on PND21 after exposure from GD10 until GD21 (Grassi et al., 2016 [RefID 2387]). This finding is supported by a Tier 3 study (Leung et al, 2017 [RefID 3990]) showing also increased numbers of TEBs at 2.5 and 25 μg/kg bw per day.…”
Section: Assessmentmentioning
confidence: 99%
“…For histological effects in this exposure period seven studies were identified, i.e. one Tier 1 study in mice (Tucker et al, 2018 [RefID 13275]), five Tier 1 studies in rats (Grassi et al, 2016 [RefID 2387]; Kass et al, 2015 [RefID 3402]; Mandrup et al, 2016 [RefID 4831]; NTP Clarity Report, 2018/Camacho et al, 2019 [RefID 11370]; Montévil et al, 2020 [RefID 13788]) and one Tier 3 study in rats (Leung et al., 2017 [RefID 3990]).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies within the mammalian stream were concerned with mammary gland development. Grassi et al (2016) [RefID #2387] aimed to evaluate the modifying effects of gestational BPA on early mammary gland development in female rat offspring. Prenatal BPA exposure induced both morphological and epigenetic gene expression modifications on the mammary gland with alterations in several genes occurring at a low BPA dose.…”
Section: (Iii) Mammary Gland Developmentmentioning
confidence: 99%
“…this cluster were concerned with the development of mammary gland. These are studies reported byGrassi et al (2016) [RefID #2387], Kas et al (2015) [RefID #3402] and Tucker et al (2018) [RefID #13275] and all have been summarised in Section 3.8.5 'Proliferative changes to the mammary gland'. (vii) Neuronal development Several studies in this cluster were concerned with neurological development.…”
mentioning
confidence: 99%